Congenital Anomalies of the Visual Organ, Congenital Blepharoptosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Congenital anomalies of the visual organ are currently the main form of ophthalmopathology in children. This is confirmed by leading specialists in pediatric ophthalmology.